"I Did It All Online:" Transgender identity and the management of everyday life. Issue 1 (1st January 2016) - Cavalcante, Andre
ABSTRACT: Informed by ethnographic work with transgender individuals and communities in the Midwest and San Francisco, this article explores the relationship between technology and transgender identity. It examines the possibilities for self-recognition that transgender audiences had before the era of the internet. Then, through a case study of a transgender person, it engages in a close analysis of what it means to transition gender in online environments. Drawing from Heidegger's (1962. Being and time . New York: Harper Perennial) phenomenology of technology, I argue that technology has become increasingly "ready-to-hand"—available, participatory, and taken-for-granted—for transgender individuals. In particular, the internet has created virtual "counterpublics" (Warner, 2002. Publics and counterpublics . Brooklyn: Zone Books) that furnish feelings of belonging and ideological affiliation, as well as "care structures" (Scannell, 2014. Television and the meaning of live: An enquiry into the human situation . Cambridge, UK: Polity Press), architectures of organized care and concern, that facilitate transgender identity work and everyday survival. For transgender individuals, who live in a world created without them in mind, the affordances of online counterpublics and care structures help them manage the trials and complexities of everyday life. At the same time, contemporary digital media environments introduce new risks and liabilities for transgender individuals.